The mediating effect of knowledge acquisition on the application of knowledge in interactions: Perceptions of ease of use, actual use, and behavioral intentions in e-learning platforms - Duche-Pérez, Aleixandre Brian; Gutiérrez-Aguilar, Olger Albino; Vera-Revilla, Cintya Yadira; Chicana-Huanca, Sandra; Andía-Gonzales, Brizard Guadalupe (Edelweiss Applied Science and Technology, 2024)
This study explores the mediating effect of knowledge acquisition on the application of knowledge within e-learning environments, focusing on key factors such as perceived ease of use, actual system use, and behavioral intention to use. In the post-pandemic context, e-learning has transitioned from a temporary solution to a fundamental aspect of higher education, necessitating an understanding of how these factors influence learning outcomes. The research employs a quantitative, non-experimental cross-sectional design, analyzing data from 235 students at the Catholic University of Santa María in Peru. Using structural equation modeling (SEM) techniques, the study reveals that perceived ease of use significantly enhances both knowledge acquisition and application, while actual use of the system has a complex relationship with learning outcomes. Behavioral intention to use the system also plays a crucial role, both directly and indirectly, in promoting effective knowledge acquisition and application. These findings underscore the importance of user-friendly e-learning platforms and proactive strategies to foster positive attitudes towards technology use, ensuring that students not only acquire but also effectively apply knowledge in their academic and professional lives. The results contribute to the ongoing discourse on optimizing e-learning systems for better educational outcomes.